Westonci.ca is the ultimate Q&A platform, offering detailed and reliable answers from a knowledgeable community. Join our platform to connect with experts ready to provide precise answers to your questions in various areas. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
[tex] \huge \boxed{\mathbb{QUESTION} \downarrow}[/tex]
- By substitution, justify that x = − 6 is a solution to x − 2 = − x − 14.
[tex] \large \boxed{\mathbb{ANSWER\: WITH\: EXPLANATION} \downarrow}[/tex]
First, let's substitute the value of x as -6 in the equation.
[tex] \tt \: x - 2 = - x - 14 \\ \dashrightarrow \: \tt \: ( - 6) - 2 = - ( - 6) - 14[/tex]
Now, let's solve it.
[tex] \tt \: ( - 6 ) - 2 = - ( - 6 ) - 14[/tex]
Subtract 2 from -6 to get -8.
[tex] \tt \: -8=-\left(-6\right)-14 [/tex]
The opposite of -6 is 6.
[tex] \tt \: -8=6-14 [/tex]
Subtract 14 from 6 to get -8.
[tex] \tt \: -8=-8 [/tex]
Compare -8 and -8. We can see that both the LHS & RHS are equal to each other. So, hence we proved that x = − 6 is a solution of x − 2 = − x − 14.
Hey there!
x - 2 = -x - 14
Substitute -6 for x (given).
x - 2 = -x - 14
= (-6) - 2 = -(-6) - 14
= -8 = +6 - 14
= -8 = -8
The Left Hand Side (LHS) is equal to the Right Hand Side (RHS).
•°• LHS = RHS, hence proved.
Hope it helps ya!
Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.